Gold nanostructures: synthesis, properties, and neurological applications. (2nd March 2022) - Zare, Iman; Yaraki, Mohammad Tavakkoli; Speranza, Giorgio; Najafabadi, Alireza Hassani; Shourangiz-Haghighi, Alireza; Nik, Amirala Bakhshian; Manshian, Bella B.; Saraiva, Cláudia; Soenen, Stefaan J.; Kogan, Marcelo J.; Lee, Jee Woong; Apollo, Nicholas V.; et al.
Abstract : Recent advances in nanotechnology are expected to increase our current understanding of neuroscience. Abstract : Recent advances in technology are expected to increase our current understanding of neuroscience. Nanotechnology and nanomaterials can alter and control neural functionality in both in vitro and in vivo experimental setups. The intersection between neuroscience and nanoscience may generate long-term neural interfaces adapted at the molecular level. Owing to their intrinsic physicochemical characteristics, gold nanostructures (GNSs) have received much attention in neuroscience, especially for combined diagnostic and therapeutic (theragnostic) purposes. GNSs have been successfully employed to stimulate and monitor neurophysiological signals. Hence, GNSs could provide a promising solution for the regeneration and recovery of neural tissue, novel neuroprotective strategies, and integrated implantable materials. This review covers the broad range of neurological applications of GNS-based materials to improve clinical diagnosis and therapy. Sub-topics include neurotoxicity, targeted delivery of therapeutics to the central nervous system (CNS), neurochemical sensing, neuromodulation, neuroimaging, neurotherapy, tissue engineering, and neural regeneration. It focuses on core concepts of GNSs in neurology, to circumvent the limitations and significant obstacles of innovative approaches in neurobiology and neurochemistry, including theragnostics. We will discuss recent advances in the use of GNSs to overcome current bottlenecks and tackle technical and conceptual challenges.